Nanopesticides: Physico-chemical characterization by a combination of advanced analytical techniques. (December 2020) - Bocca, B.; Barone, F.; Petrucci, F.; Benetti, F.; Picardo, V.; Prota, V.; Amendola, G.
Abstract: The recent application of manufactured nanomaterials (MNMs) in plant protection products (PPPs) enhances stability of the active substance (a.s.), minimizes application losses, reduces the quantities of a.s., increases coverage on leaf surface, improves precise application, etc. Besides offering benefits, there is high concern about the potential risk for human and environment associated with the use of nanopesticides. In this study, a panel of complementary methodologies were used to determine size distribution and chemical identification of four different formulations of nanopesticides. Measurements were performed by dynamic light scattering (DLS), transmission electron microscopy (TEM), asymmetric field flow fractionation-multi angle light scattering (AF4-FFF-MALS), gas/liquid chromatography with mass spectrometry (GC-MS/MS, LC-MS/MS) or diode array detector (HPLC-DAD) and inductively coupled plasma mass spectrometry (ICP-MS). Results indicated average size values in the ranges: 27.4–148.7 nm by DLS; 39.1–82.0 nm by AF4-FFF-MALS; and 42–90 nm by TEM. Linked to these nanosized particles both organic active ingredients and inorganic ones were identified. In addition, the obtained data revealed that all the four PPPs contained more than 50% of particles with number size distribution between 1 and 100 nm and, according to the European Commission definition, they can be defined as nanopesticides. Graphical abstract: Image 1 Highlights: Risks of nanomaterials used in plant protection products (PPPs) are still unknown. Different formulations of PPPs were analysed applying state-of-the-art techniques in a tiered approach. PPPs formulations contained more than 50% in number of particles smaller than 100 nm. Results provided the basis for the exposure assessment to PPPs nanoformulations.